Poling temperature‐insensitive piezoelectric constant of high‐performance potassium sodium niobate piezoceramics. Issue 8 (28th April 2020) - Tao, Hong; Wang, Zheng; Zhao, Silu; Zhao, Chunlin; Yin, Jie; Wu, Jiagang
Abstract: Deriving from strong temperature dependence of polymorphic phase boundaries, piezoelectric constant of potassium sodium niobate (K0.5 N0.5 NbO3 )‐based ceramics is sensitive to the poling temperature. Here, an effective strategy of doping rare earth (RE) elements is proposed to solve this issue. Piezoelectric constant ( d 33  ~ 440 pC/N) can be well kept in 0.965K0.45 Na0.55 Nb0.96 Sb0.04 O3 ‐0.035(Bi0.75 Dy0.25 )0.5 Na0.5 HfO3 ceramics at a wide poling temperature range (35‐120°C) by the method of replacing Bi 3+ with rare earth dysprosium, and importantly, this method can be effectively expanded to other RE elements. The high piezoelectricity roots in the multiphase coexistence with the addition of RE elements. The dull sensitivity of poling temperature is analyzed by microstructure information, that is, ferroelectric domains can be well rotated under a wide temperature range by introducing RE, which is responsible for the stabilized piezo‐response against the poling temperature. Moreover, comparing with Bi 3+, a lower electronegativity of RE 3+ may effectively reduce the micro‐stress produced by lattice distortion, also yielding to the lattice softening and the easier domain rotation. Abstract : Wide poling temperature range of KNN ceramics with high piezoelectric constant can be realized by doping rare earth elements, originating from lower electronegativity of RE 3+ than Bi 3+ which is benefit of reducing the micro‐stress produced by lattice distortion, also yielding to the lattice softening and the easier domain rotation..